Pengaruh Laju Alir Umpan Terhadap Efisiensi Penyisihan Padatan Dalam Limbah Cair Pulp Dan Kertas Dengan Reaktor Kontsk Stabilisasi - Elfina Noviarni Chandra; Adrianto Ahmad; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
High consumption of paper both globally and nationally have pushed pulp and paper industry to increase its production capacity from year to year. This resulted the wastewater produced in large quantities. Characteristics of solids in pulp and paper wastewater includes TS (Total Solid), TVS (Total Volatile Solid), TSS (Total Suspended Solid) and VSS (Volatile Suspended Solid) respectively are 0,7; 0,28; 0,6; 0,26 g/L. Solids in the wastewater is a material adverse impact on water quality, such as reducing sunlight penetration into bodies of water, increasing the turbidity of water, can lead to impaired growth for organism and solubility of oxygen in water. Solids handling of pulp and paper wastewater can be aerobically by using stabilization contact reactor. The purpose of this research is to removing the content of solids in pulp and paper wastewater and determine the effect of feed flow rate of solids removal efficiency and biomass concentration on stabilization contact reactor. The conditions of this research is detention time in stabilization tank is 4 hours, sludge age 15 days and % resirculation is 75% of influent flow. The results showed that the solids removal includes TS, TVS, TSS and VSS by varying feed flow rate for 2,2 L/hour, 2,9 L/hour, 4,4 L/hour and 8,8 L/hour, the highest solids removal efficiency obtained at 2,2 L/hour respectively are 72,38%, 69,05%, 79,26% and 74,36%. This suggests that the stabilization contact reactor is stabilized in removing solids content of pulp and paper wastewater.Keyword: Aerobic, Content of Solids, Pulp and Paper Wastewater, Reactor Contacts Stabilization.